The relationship between corporate social responsibility and financial performance : a multiple case study of Finnish retailers - Heikkilä, Laura (My University, 2022)
Corporate social responsibility (CSR) has constantly gained more attention among companies, scholars, and consumers alike in the past decades. While CSR has a broad base of definitions, scholars seem to agree that it can be seen as companies’ responsibility economically, socially, and environmentally. However, despite the growing importance of the topic, some also see CSR to conflict with the very essence of business – making profit. Various scholars have conducted research around the relationship between corporate social responsibility and financial performance, but a clear consensus has not been reached. This study aims to analyze the relationship between CSR and financial performance in the context of Finnish retail companies by conducting thorough case analyses on three significant retailers in the Finnish retail market. The multiple case study is conducted through thematic analysis based on a theoretical framework that was established based in the literature re-view. The case companies, S-Group, K-Group, and Tokmanni, are analyzed in terms of their sustainability actions, disclosure, and corporate social reputation. These aspects are then reflected and compared with their financial performance during the observation period of 2019–2021. Financial performance is reviewed on accounting-based and market-based metrics. The three companies give a holistic sight over the Finnish retail context, as they represent the majority market share of the industry. Data is collected from secondary sources, such as financial reports and sustainability reports of the focal case companies. The findings of this study support the point of view that a clear-cut relationship between CSR and financial performance is difficult to identify. While S-Group and K-Group have more ad-vanced CSR actions and are perceived as clearly more sustainable by consumers, they show very differing financial performance during the observation period. While K-Group has shown robust growth on all financial measures, S-Group faces a declining trend on its ac-counting-based measures. Simultaneously Tokmanni with slightly less developed CSR actions and the lowest ranking on consumer perception has performed financially extremely well on both accounting-based and market-based metrics. Thus, the findings of this study do not prove a positive or a negative relationship between CSR and financial performance within the Finnish retail industry. However, the extent of CSR measures taken by the companies seems to highly affect the corporate social reputation of the companies in the eyes of consumers.
Keywords: corporate responsibility; retail trade; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development